Desenvolvimento de medidor de vazão de gás por ultra-som: modelagem, protótipo e testes - Ramos, Rodrigo (2006)
The use of transit time ultrasonic flow measurement technique has increased very quickly in the last years, so that it is urgently necessary to develop Brazilian technology in this instrumentation field. This work presents the development of a transit time flow meter prototype, called MEVUS, devoted to measurement of gas flows. It presents the mathematical modeling of the governing physical process of the interaction between the ultrasonic wave and the flow that one wants to measure, which is supposed completely developed in a circular pipe. It also presents a systematization of the uncertainty analysis related to the measurement process. The process of conception, analysis and design of the prototype is equally described, so that the reader can easily understand the problems found during the development, highlighting the proposed solutions and the feedback of the creation process of MEVUS Medidor de Vazão por Ultra-Som (Ultrasonic Flowmeter). Performance tests were conducted in the Flow Machines Laboratory of the Mechanical Engineering Department UFES. They are clearly described. The conclusions are presented, as well as the suggestions for future works